Circumgalactic medium on the largest scales: detecting X-ray absorption lines with large-area microcalorimeters - Bogdán, Ákos; Khabibullin, Ildar; Kovács, Orsolya E.; Schellenberger, Gerrit; ZuHone, John; Burchett, Joseph N.; Dolag, Klaus; Churazov, Eugene; Forman, William R.; Jones, Christine; Kilbourne, Caroline; Kraft, Ralph P.; et al. (The astrophysical journal, 2023)
The circumgalactic medium (CGM) plays a crucial role in galaxy evolution as it fuels star formation, retains metals ejected from the galaxies, and hosts gas flows in and out of galaxies. For Milky Way-type and more-massive galaxies, the bulk of the CGM is in hot phases best accessible at X-ray wavelengths. However, our understanding of the CGM remains largely unconstrained due to its tenuous nature. A promising way to probe the CGM is via X-ray absorption studies. Traditional absorption studies utilize bright background quasars, but this method probes the CGM in a pencil beam, and, due to the rarity of bright quasars, the galaxy population available for study is limited. Large-area, high spectral resolution X-ray microcalorimeters offer a new approach to exploring the CGM in emission and absorption. Here, we demonstrate that the cumulative X-ray emission from cosmic X-ray background sources can probe the CGM in absorption. We construct column density maps of major X-ray ions from the Magneticum simulation and build realistic mock images of nine galaxies to explore the detectability of X-ray absorption lines arising from the large-scale CGM. We conclude that the O VII absorption line is detectable around individual massive galaxies at the 3σ-6σ confidence level. For Milky Way-type galaxies, the O VII and O VIII absorption lines are detectable at the ∼ 6σ and ∼ 3σ levels even beyond the virial radius when coadding data from multiple galaxies. This approach complements emission studies, does not require additional exposures, and will allow for probing the baryon budget and the CGM at the largest scales.
Online veröffentlicht: 1. August 2023
Gesehen am 11.10.2023